Peran Wanita Muslim dalam Meminimalisir Kekerasan dalam Rumah Tangga - Patmawati Patmawati; Fitri Sukmawati (PSGA LP2M IAIN Pontianak, 2015)
Islam is the graceful religion that gives the rules towards women about how they act to their husband in domestic environment in order to build the togetherness fairly. Not to mention in the marriage life, the roles of wives are very important. They should behave politely, sweetly, kindly, and full of love and trust to their husband. Besides, a wife also should try to possess the adorable acts towards the husband. Moreover, as a mother for her children, a woman should also able to afford the rights and obligations to the children based on their physical dan psychological development, so that the children could contribute to the religion, country, and their nation.